Country data on AMR in Saudi Arabia in the context of community-acquired respiratory tract infections: links between antibiotic susceptibility, local and international antibiotic prescribing guidelines, access to medicine and clinical outcome. (6th September 2022) - Torumkuney, Didem; Dolgum, Saeed; van Hasselt, James; Abdullah, Walid; Keles, Nergis
Abstract: Background: Antimicrobial resistance (AMR) is one of the biggest threats to global public health. Selection of resistant bacteria is driven by inappropriate use of antibiotics, amongst other factors. COVID-19 may have exacerbated AMR due to unnecessary antibiotic prescribing. Country-level knowledge is needed to understand options for action. Objectives: To review AMR in Saudi Arabia and initiatives addressing it. Identifying areas where more information is required will provide a call to action to minimize a further rise in AMR within Saudi Arabia and improve patient outcomes. Methods: National AMR initiatives, antibiotic use and prescribing, and availability of susceptibility data, particularly for the key community-acquired respiratory tract infection (CA-RTI) pathogens Streptococcus pneumoniae and Haemophilus influenzae, were identified. National and international antibiotic prescribing guidelines commonly used locally for specific CA-RTIs (community-acquired pneumonia, acute otitis media and acute bacterial rhinosinusitis) were also reviewed, plus local antibiotic availability. Insights from a clinician in Saudi Arabia were sought to contextualize this information. Conclusions: Various initiatives are underway in Saudi Arabia, including a National Action Plan for AMR, which was published in 2017. However, AMR is rising and knowledge about appropriate antibiotic use seems to be lacking among physicians and the general public. Various international guidelines are utilized by clinicians in Saudi Arabia, but a more standardized inclusive approach in developing local guidelines, using up-to-date surveillance data of isolates from community-acquired infections in Saudi Arabia could make management guideline use more locally relevant for clinicians. This would pave the way for a higher level of appropriate antibiotic prescribing and improved adherence. This would, in turn, potentially limit AMR development and improve patient outcomes.